2016
DOI: 10.1016/j.jped.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between nutritional status and outcomes in critically-ill pediatric patients – a systematic review

Abstract: The studies included in this review suggest that nutritional depletion is associated with worse outcomes in pediatric intensive care units. However, studies are scarce and those existing show no methodological homogeneity, especially regarding nutritional status assessment and classification methods. Contemporary and well-designed studies are needed in order to properly assess the association between children's nutritional status and its impact on outcomes of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
15
2
Order By: Relevance
“…After confirmation of eligibility, a quality questionnaire was prepared by the authors of the study based on the methodological procedures indicated by Armstrong et al (15) , Murad et al (16) and Costa et al (17) (Chart 1). The questionnaire consisted of ten items, with "yes" or "no" answers on clarity in the identification of objectives, ethical aspects, methodological adequacy (sampling, selection/ recruitment of participants and data collection), statistical analysis, presentation/interpretation of results, limitations and contributions of the study.…”
Section: Eligibility Of Studiesmentioning
confidence: 99%
“…After confirmation of eligibility, a quality questionnaire was prepared by the authors of the study based on the methodological procedures indicated by Armstrong et al (15) , Murad et al (16) and Costa et al (17) (Chart 1). The questionnaire consisted of ten items, with "yes" or "no" answers on clarity in the identification of objectives, ethical aspects, methodological adequacy (sampling, selection/ recruitment of participants and data collection), statistical analysis, presentation/interpretation of results, limitations and contributions of the study.…”
Section: Eligibility Of Studiesmentioning
confidence: 99%
“…It is important to note that the data available in regard to the relationship between nutritional status and clinical outcomes, such as those used in the present study, have originated from observational studies; therefore, it is difficult to draw conclusions due to the heterogeneity and limitations of those studies. ( 11 )…”
Section: Discussionmentioning
confidence: 99%
“…Patients in a PICU with nutritional status inadequacies can experience unfavorable outcomes (i.e., mechanical ventilation - MV, mortality, longer length of stay and infection); therefore, it is extremely important to assess the unit's nutritional profile. ( 11 )…”
Section: Introductionmentioning
confidence: 99%
“…Critically ill neonates and children who receive sufficient nutrition have reduced complications, spend less time on mechanical ventilation, reduced time in intensive care and have overall improved health outcomes [1][2][3][4][5]. Nutrition should, if at all possible, be delivered enterally to maintain gut barrier function [6].…”
Section: Introductionmentioning
confidence: 99%